Determination of shoulder global range of motion - Liew, Wei Hao (2017)
The objective of this study is to quantify the shoulder global range of motion in three dimensions and for activities of daily living. Forty-five male and five female participants with no prior shoulder injuries participated in this study. Six standard shoulder range of motion, four movements simulating activities of daily living and an extreme range of motion, were performed in an optical marker-based motion capture system. Markers were positioned in accordance to the thorax and humerus coordinate system as recommended by the International Society of Biomechanics. The chest harness used in previous studies to facilitate motion capture for females caused significant deviation for one of the markers during shoulder movement, so females were instructed to wear sports bra in this study. Euler angles obtained from the rotation sequence between the joint coordinate systems, namely the angle of elevation and angle of plane of elevation, were used to quantify and compare the shoulder range of motion. Comparison on both angles from each movement was done between male and female participants with the Student’s t-test at 95% confidence level. The t-tests conducted on three out of the twelve angles for standard range of motion, and four of the eight angles for activities of daily living, had p-values of less than 0.05, meaning that they were statistically significant. For extreme shoulder range of motion, the Euler angles were used as spherical coordinates to plot on a three-dimensional globe. With this method, it is easier to visualise the extreme range of motion in three dimensions and compare between different subjects with reference to the latitudes and longitudes. Future studies can make use of this method to quantify both standard and functional shoulder range of motion in three dimension.